A case study on the effect of biocompost on oil palm plantation yield at Felda Sahabat 11, Lahad Datu, Sabah / Musran Usman (Faculty of Plantation and Agrotechnology, 2016)
Palm oil production is the main agricultural industry in Malaysia, in which palm oil mill effluent (POME) and oil palm empty fruit bunch (EFB) are considered as significant waste products from the palm oil industry. These waste products make an environmental hazard and involve high transfer costs each year. Composting is an organically based procedure which is practiced to balance out the organic matter for soil change (delivering compost) and to shield the earth from the inconvenient impacts of these waste products and also to increase the crop production. This case study was reviewed on the effect of biocompost (EFB and POME) application on oil palm yield from year 2012 until year 2015 and there are differences towards effect between with and without the application of biocompost. As a result, there is a significant difference between the yield after application and before application of biocompost. In addition, the study reviews on the explanation about bioconversion of EFB and POME into Compost (Biocompost).